In vitro antithrombotic properties of salmon (salmo salar) phospholipids in a novel food-grade extract - ALEXANDROS TSOUPRAS; Ronan Lordan; Katie Shiels; Sushanta Kumar Saha; Constantina Nasopoulou; IOANNIS ZABETAKIS (2019)
Marine and salmon polar lipids (PLs) extracted by conventional extractions with non-food-grade solvents (CE-salmon-PLs) possess antithrombotic bioactivities against platelet-activating factor (PAF) and thrombin. Similar effects of food-grade-extracted (FGE) marine PLs have not yet been reported. In this study, food-grade solvents were used to extract PLs from Irish organic farmed salmon (Salmo salar) fillets (FGE-salmon-PLs), while their antithrombotic bioactivities were assessed in human platelets induced by platelet aggregation agonists (PAF/thrombin). FGE-salmon-PLs were further separated by thin layer chromatography (TLC) into lipid subclasses, and the antithrombotic bioactivities of each subclass were also assessed. LC-MS was utilized to elucidate the structure-activity relationships. FGE-salmon-PLs strongly inhibited PAF-induced platelet aggregation, while their relevant anti-thrombin effects were at least three times more potent than the previously reported activities of CE-salmon-PLs. TLC-derived lipid fractions corresponding to phosphatidylcholines (PC) and phosphatidylethanolamines (PE) were the most bioactive lipid subclasses obtained, especially against thrombin. Their LC-MS analysis elucidated that they are diacyl- or alkyl-acyl-PC and PE moieties baring !3 polyunsaturated fatty acids (PUFA) at their sn-2 position, such as eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA). Our results concerning the potent antithrombotic effects of FGE-salmon-PLs against both PAF and thrombin pathways strongly suggest that such food-grade extracts are putative candidates for the development of novel cardioprotective supplements and nutraceuticals.